2017
DOI: 10.1016/j.ophtha.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Causes of Vision Loss in Indigenous and Non-Indigenous Australians

Abstract: Vision loss is more prevalent in Indigenous Australians than in non-Indigenous Australians, highlighting that improvements in eye healthcare in Indigenous communities are required. The leading causes of vision loss were uncorrected refractive error and cataract, which are readily treatable. Other countries with Indigenous communities may benefit from conducting similar surveys of Indigenous and non-Indigenous populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 51 publications
1
89
1
Order By: Relevance
“…Subsequently, this population is twice as likely to be hospitalized for injury compared to the non‐Indigenous population, the most common injury being falls and assault . The NT has the highest proportion of Indigenous individuals in its population of any state . RDH services a population of 183 708 of which several remote and rural Indigenous communities are included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, this population is twice as likely to be hospitalized for injury compared to the non‐Indigenous population, the most common injury being falls and assault . The NT has the highest proportion of Indigenous individuals in its population of any state . RDH services a population of 183 708 of which several remote and rural Indigenous communities are included.…”
Section: Discussionmentioning
confidence: 99%
“…14 The NT has the highest proportion of Indigenous individuals in its population of any state. 11,14,15 RDH services a population of 183 708 of which several remote and rural Indigenous communities are included. Wong et al, in a suburban based study, demonstrated that males were more likely than females to be affected by ocular trauma in a 5-y prevalence study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of diabetes-related vision impairment, although varying widely between 5.2% to as high as 26.5% depending on the study context, sampling methodology and region, is consistently reported to be higher among Indigenous Australians [14][15][16]. Among non-Indigenous Australians, diabetic complications contribute only 1.7% of the total burden of vision impairment and these rates have remained largely unchanged over a twenty-year timespan [12,17]. The increasing availability of highly effective but expensive sight-saving treatments (i.e., intravitreal anti-vascular endothelial growth factor or corticosteroid drugs), improved overall diabetes and risk factor control, and access to a range of DR screening programs are likely to have played a role in this stability [18].…”
Section: Diabetic Retinopathy Among Indigenous Australiansmentioning
confidence: 99%
“…For the Indigenous people of Australia, the ongoing impact of colonisation and continuing social and political oppression and dispossession have contributed to significant socio-economic and health inequities across several key health indicators [9]. T2DM is one of the most important contributors to health inequities (both mortality and morbidity) between Indigenous and non-Indigenous Australians, as it is a potent driver of premature onset cardiovascular, renal and retinal complications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the results of the Australian National Eye Health Survey (NEHS) reported in 2017 that the main cause of vision impairment continued to be uncorrected refractive error corresponding to 61% of the total . Notably, while the overall prevalence of vision loss in Australia was reported at 6.6%, there was a marked contrast in prevalence of vision loss between non‐Indigenous Australians at 6.5% compared to Indigenous Australians at 11.2% . The main contributing risk factors for vision loss in non‐Indigenous Australians were increasing age (odds ratio [OR], 1.72 per decade) and not having had an eye examination within the past year (OR, 1.61).…”
mentioning
confidence: 99%